Art For God's Sake - "Ryken, Philip Graham"
"Includes bibliographical references (p. 59-64). Art and the church -- The artist's calling -- All kind of art -- The good, the true, and the beautiful -- Art for the glory of God -- Beautiful Savior."
Keywords: CHRISTIANITY AND ART